The Use of Politeness Strategies in Whatsapp Discussions about Sensitive Topics - Junita Junita (Journal of English Language and Culture, 2020)
The studies about language use in the past several years showed the existence of gender inequalities. According to Lakoff (1975), women are pressured to show the feminine qualities of weakness and frequently subordinate status toward men in a male-dominated society. However, nowadays, women's position in society is equal to men's position. The evidence that women are now equal to men invites the writer to study men's and women's language features and the politeness strategies used by men and women, especially in CMC (Computer-Mediated Communication). This study was a Qualitative Content Analysis (QCA) study used to describe the meaning of qualitative data systematically. The result did not align with the previous studies: it showed that women were also aggressive when giving an argument, and politeness strategies were not the most used in the forum discussion; it was bald of record instead. In sum, Herring's (1993) features of women's and men's language were not valid in this study, and some of them need to be revised. Further studies about politeness strategies in CMC should be explored more.